SARCOSPORIDIA OF DOMESTIC ANIMALS OF KUVA DISTRICT OF FERGANA REGION AND THEIR SPECIES COMPOSITION - Kh. M. Komilova; O. I. Qayumova; M. F. Bekchonova (American Journals Publishing, 2022)
Internal organs of domestic animals (cattle, sheep and goats) living in different ecological conditions of Kuva district of Fergana region (neck, muscles, esophagus, tongue, heart, diaphragm, and liver, lungs, kidneys, and spleen).
Keywords: Sarcocyst, sarcocytosis, cyst, trophozoite, scorocyst, ocyst, parasite